The Advances Of Transformation On The Fatwa Of The National Syariah Council (DSN) - Indonesian Ulema Assemblies (MUI) Number 13/Dsn-Mui/2000 Concerning Advances In Murabahah - Ali Akbar; Elga Marza Fauziah (Doctoral Program of Social Science Pasundan University, 2025)
In the study of fiqh, the advances are called by urbun. Mufties have different disagreements about the legal status of the low of urbun. Whether it belongs to a lowful or lowful contract. The majority of muftis said that advance transaction (urbun) was legal, but according to Imam Ahmad and his adherents, advance transaction (urbun) was legal. The fatwa DSN 13/DSN-MUI/2000 that there is legal transformation in establishing fatwa for advances in murabahah. The deal set of the problem was how to cross the opinion of fuqoha about the status of the advances transaction (urbun), what is the concept of advances in murabahah in the Fatwa DSN 13/DSN-MUI/2000 and the DSN-MUI istinbat method in establishing a fatwa on advances in murabahah, and how is the transformation used bay DSN (National Syariah Council) in establishing fatwa on advances in murabahah. The process of transforming advances on the fatwa DSN Number 13/DSN-MUI/2000 about the advances of murabahah, where is the opinion of the participants of the National Sharia Council (DSN) plenary meeting together with the financial accounting standards of Indonesian accounting on Saturday, 7 Rabi'u awwal 1421 H./16 September 2000 th and the opinion of the participants of the plenary meeting of the national sharia council on the 17 th day of Jumadil Akhir 1421 H./16 September 2000, decide and set a fatwa on advances in murabahah. The formation of a fatwa on the national sharia council is one of the planned transformations which means that the transformation of the formation of the national sharia council does not just happen, but through the planning stages. The method used in this research is descriptive method. While the data used is a set of DSN_indonesian ulema assemblies (MUI), especially the national syariah council 13/DSN_MUI/2000 concerning advances in murabahah, as well as books fiqh that support in this research as a secondary source. As for the techniques used to collect data is a study of decisions or literature studies. The cross of the fuqoha opinions contradicting each other, then the stongest opinion among the two opinions is the opinion that allows the urbun transaction. (DSN_MUI) is that there are several transformations such as change transformation, object cultural transformation, transformation of structural and form transformation.